(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The objective of this study was to evaluate association of anticardiolipin IgM antibody with preeclampsia among the 70 pregnant women having preeclampsia from March 2016 to February 2017. Equal number of age matched normotensive healthy pregnant women was selected as control. Demographic, obstetric and relevant laboratory data were collected and compared between the two groups. The level of anticardiolipin IgM antibody was significantly higher in preeclamptic women than in normal pregnant (mean 8.7 vs 5.8 U/mL, p<0.001). Even in categorical distribution when the value was considered as positive by assessing a cut-off, cases had three times more chance to have positive level of anticardiolipin IgM antibody than controls (OR=3.3, 95% CI=1.1-9.6, p=0.046). Pearson’s correlation test revealed that both systolic and diastolic blood pressure had a positive correlation with the level of anticardiolipin IgM antibody. (p<0.05). In conclusion, this study shows that anticardiolipin IgM antibody was associated with preeclampsia. The level of this anticardiolipin IgM antibody is directly proportional to the severity of preeclampsia and both systolic and diastolic blood pressure.